2019
DOI: 10.1038/s41386-019-0428-2
|View full text |Cite|
|
Sign up to set email alerts
|

Functional brain networks in never-treated and treated long-term Ill schizophrenia patients

Abstract: This study compared the topological organization of brain function in never-treated and treated long-term schizophrenia patients. In a cross-sectional study, 21 never-treated schizophrenia patients with illness duration over 5 years, 26 illness duration-matched antipsychotic-treated patients and 24 demographically-matched healthy controls underwent a resting-state functional magnetic resonance imaging (MRI) scan. The topological properties of brain functional networks were compared across groups, and then we t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 70 publications
1
10
1
Order By: Relevance
“…It should be noted that unlike our previous findings that long-term untreated patients showed more severe deficits in the white matter 17 and functional networks 48 than treated patients, our findings revealed more regions with reduced GM in treated patients than untreated patients. One of the possible explanations is that the mechanism of antipsychotics may be associated with GM reductions and functional performance improvements.…”
Section: Discussioncontrasting
confidence: 99%
“…It should be noted that unlike our previous findings that long-term untreated patients showed more severe deficits in the white matter 17 and functional networks 48 than treated patients, our findings revealed more regions with reduced GM in treated patients than untreated patients. One of the possible explanations is that the mechanism of antipsychotics may be associated with GM reductions and functional performance improvements.…”
Section: Discussioncontrasting
confidence: 99%
“…The observed reduction in centrality across core hubs with a smaller magnitude of increase in centrality in other regions is also consistent with many prior observations of reduced degree centrality 29 31 , though Tang et al 32 reported no centrality reductions in schizophrenia. Tang and colleagues studied a relatively younger age group of subjects with >50% medicated for an unspecified amount of time; and considered only positive values of functional connectivity to quantify centrality.…”
Section: Discussionsupporting
confidence: 89%
“…Both increased ( Reis Marques et al, 2014 ) and decreased FA ( Wang et al, 2013 ; Szeszko et al, 2014 ) as well as no evidence for whiter matter changes ( Kraguljac et al, 2019 ) after short-term (6–12 weeks) antipsychotic treatment have been reported. Clinical studies on long-term antipsychotic treatment, including our previous studies ( Xiao et al, 2018 ; Yao et al, 2019 ), suggest that antipsychotic medications may have beneficial effects on the brain’s structure and function. In contrast, studies on non-human primate models have suggested adverse effects of antipsychotics by reporting associations between chronic exposure to antipsychotics with reduced brain volume and glial cell numbers ( Dorph-Petersen et al, 2005 ; Konopaske et al, 2007 ).…”
Section: Discussionmentioning
confidence: 78%
“…This suggests that long-term antipsychotic treatment does not adversely affect the brain’s structure over the longer term course of illness and may even confer some benefits ( Xiao et al, 2018 ). The potential beneficial effects of long-term antipsychotic treatment are additionally supported by functional brain imaging data ( Yao et al, 2019 ). However, previous studies reporting brain structure alterations in antipsychotic-treated patients were limited by very diverse antipsychotic treatments, which did not allow specific conclusions about specific effects of individual agents on white matter brain structure ( Bartzokis et al, 2007 , 2009 ; Vita et al, 2015 ; Leroux et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%